Mental health and financial problems: A bibliometric study - Ramadhani, Erfan; Indreswari, Henny; Janu Setiyowati, Arbin; Darma Putri, Ramtia; Siska Pratiwi, Awalya (Journal of Advanced Guidance and Counseling, 2025)
Purpose – This study examines the relationship between financial stress and mental health, focusing on adaptation mechanisms and the socio-cultural factors influencing resilience. It also identifies key research trends, emerging themes, and global collaborations. Method – A bibliometric analysis was conducted on 488 articles from the Scopus database (2019–2024). The study employed multiple linear regression and path analysis to assess the effects of financial stress on mental health, with socio-cultural factors as an intervening variable. A sample of 100 individuals was selected using a simple random sampling method. Data analysis was performed using R software and the Biblioshiny application, incorporating keyword analysis, research collaboration mapping, and thematic classification. Result – The findings indicate a significant increase in research on financial stress, mental health, and coping strategies. Cross-country collaborations have strengthened, particularly among the United States, the United Kingdom, and China. Emerging topics such as financial resilience and adaptive strategies are gaining attention. The study highlights the complex relationship between financial stress and mental well-being, influenced by economic conditions and social support systems. Implication – The study suggests integrating financial and psychological interventions to enhance coping mechanisms and improve societal well-being, offering insights for policymakers. Originality/Value – This research is the first to incorporate socio-cultural factors as an intervening variable, providing a comprehensive framework for understanding financial stress and mental health. *** Tujuan – Studi ini mengkaji hubungan antara stres keuangan dan kesehatan mental, dengan fokus pada mekanisme adaptasi dan faktor-faktor sosio-budaya yang memengaruhi ketahanan. Studi ini juga mengidentifikasi tren penelitian utama, tema-tema yang muncul, dan kolaborasi global. Metode – Analisis bibliometrik dilakukan pada 488 artikel dari basis data Scopus (2019–2024). Studi ini menggunakan regresi linier berganda dan analisis jalur untuk menilai dampak stres keuangan terhadap kesehatan mental, dengan faktor sosio-budaya sebagai variabel perantara. Sebuah sampel terdiri dari 100 individu dipilih menggunakan metode sampling acak sederhana. Analisis data dilakukan menggunakan perangkat lunak R dan aplikasi Biblioshiny, yang mencakup analisis kata kunci, pemetaan kolaborasi penelitian, dan klasifikasi tematik. Hasil – Temuan menunjukkan peningkatan signifikan dalam penelitian tentang stres keuangan, kesehatan mental, dan strategi koping. Kolaborasi antar negara semakin kuat, terutama antara Amerika Serikat, Inggris, dan China. Topik-topik baru seperti ketahanan keuangan dan strategi adaptif mulai mendapat perhatian. Studi ini menyoroti hubungan kompleks antara stres keuangan dan kesejahteraan mental, yang dipengaruhi oleh kondisi ekonomi dan sistem dukungan sosial. Implikasi – Studi ini menyarankan integrasi intervensi keuangan dan psikologis untuk meningkatkan mekanisme penanggulangan dan meningkatkan kesejahteraan masyarakat, memberikan wawasan bagi pembuat kebijakan. Orisinalitas/Nilai – Penelitian ini merupakan yang pertama kali memasukkan faktor sosio-budaya sebagai variabel perantara, menyediakan kerangka kerja komprehensif untuk memahami stres keuangan dan kesehatan mental.